Treatment of pancreatic fistula after cephalic duodenopancreatectomy - Juárez-Granda, Héctor (2025)
Postoperative pancreatic fistula (POPF) is the most common complication after cephalic pancreatoduodenectomy (CPD) and occurs in 3 to 45% of cases. It is associated with morbid sequelae including intra-abdominal sepsis, hemorrhage, among other. Which carries a high mortality up to 40%. Surgery is the best option in severe cases. Different surgical procedures have been tried for its treatment with different results. We present the case of a 60-year-old male patient who presented POPF after CPD and a wirsungostomy was performed as a bridge surgery until a pancreatogastro anastomosis was performed as definitive treatment.